2019
DOI: 10.1063/1.5124876
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional vortical structures and wall shear stress in a curved artery model

Abstract: We numerically investigate spatial and temporal evolution of multiple three-dimensional vortex pairs in a curved artery model under a fully developed pulsatile inflow of a Newtonian blood-analog fluid. We discuss the connection along the axial direction between regions of organized vorticity observed at various cross sections of the model, extending previous two-dimensional analysis. We model a human artery with a simple, rigid 180° curved pipe with circular cross section and constant curvature, neglecting eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…[39][40][41][42][43][44][45][46] Details on the current flow solver are provided in Cox et al [47][48][49] and Cox. 50 A grid spacing h and polynomial p convergence study was performed 12 where we found that a mesh containing a total of 69 888 hexahedral elements and a p = 4 Lagrange polynomial used to approximate the solution in each element provide ample spatial resolution (∼8.7M degrees of freedom) to converge the L 2 -norm of the error in the wall shear stress to within 0.78% and the velocity magnitude to within 0.25%. We use the free 3-D finite element mesh generator GMSH 51 to create all computational domains.…”
Section: B Numerical Schemementioning
confidence: 99%
See 3 more Smart Citations
“…[39][40][41][42][43][44][45][46] Details on the current flow solver are provided in Cox et al [47][48][49] and Cox. 50 A grid spacing h and polynomial p convergence study was performed 12 where we found that a mesh containing a total of 69 888 hexahedral elements and a p = 4 Lagrange polynomial used to approximate the solution in each element provide ample spatial resolution (∼8.7M degrees of freedom) to converge the L 2 -norm of the error in the wall shear stress to within 0.78% and the velocity magnitude to within 0.25%. We use the free 3-D finite element mesh generator GMSH 51 to create all computational domains.…”
Section: B Numerical Schemementioning
confidence: 99%
“…The numerical solver requires that a velocity field u be specified at the inlet boundary to the computational domain. Under WEC, this velocity field is extracted from PIV data captured upstream of the curvature 12 in the straight section of the pipe where the flow is fully developed pulsatile flow, where the only non-zero component of the velocity field is the streamwise velocity. These PIV data were obtained over a discretized set of 100 phases over the entire waveform period.…”
Section: Womersley Entrance Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…Einstein (1926) also noted the influence of secondary flows in the accumulation of tea leaves swept into the centre of a cup after stirring has ceased. The enhanced shear stress induced by a secondary flow also has implications for hemodynamics in cardiovascular systems (Siggers & Waters 2008; Cox, Najjari & Plesniak 2019), hence the vast body of research associated with this area. The mixing in the heat exchanger and particle erosion/deposition (Inthavong 2019) in a curved pipe arising from secondary flow has a substantial impact on power loss in the industrial piping system.…”
Section: Introductionmentioning
confidence: 99%